Advancing spatial simulations in agriculture: introducing GSSAT2, an enhanced DSSAT-Based tool - Bombana, Nathan Postal (2023)
The Decision Support System for Agrotechnology Transfer (DSSAT) is a set of tools for widely known simulation of plant growth and development; it accumulates research, contributions and validations through decades of use and development. Worldwide, DSSAT plays an important role for research into areas such as climate change and food security. A major limitation of DSSAT is its difficulty in working in geospatial contexts; it is designed to perform simulations based on isolated input data, without the ability to contextualize them in a geographic space. Previously, the International Fertilizer Development Center (IFDC) introduced the Geographic Information Support System for Agrotechnology Transfer (GSSAT), a DSSAT-based tool for conducting geospatial simulations in grid format. However, GSSAT eventually became technologically obsolete, which implies the impossibility of using it in modern systems. This job introduces GSSAT2: a web tool, designed to succeed GSSAT, also adding important features such as autonomous data collection and parallelism between simulations. The techniques and technologies used in development allowed us to develop a robust and easy-to-maintain platform capable of running simulations based on DSSAT in geospatial contexts, also leaving room for implementation of improvements and the rapid development of new functionalities due to the tooling used.